Tracking hemopexin intracellularly and defining hemopexin protein “interactomes” in human immune and liver cell models - Rose, Bryan; Moore, David; Eskew, Jeff; Vanacore, Roberto; Hartson, Steve D.; Province, Dennis; Skaff, D. Andrew; Smith, Ann (Frontiers in Physiology, 2025)
Maintaining hemopexin (HPX) plasma levels protects against heme-activated inflammation as well as the toxicity of heme and its iron during hemolysis. Plasma heme regulates HPX turnover in hepatocytes, thus controlling plasma HPX concentration. Heme from heme–HPX is delivered to the liver, and apo-HPX recycles without degradation. The scavenger receptor, low-density lipoprotein-related protein 1 (LRP1), binds heme–HPX and targets it for lysosomal degradation. Nevertheless, heme–HPX endocytosis also occurs in mouse embryonic fibroblast LRP1−/−PEA 13 cells. Therefore, the cell biology of heme–HPX endocytosis requires elucidation. We have identified candidate HPX receptors and human proteins that bind to heme–HPX, i.e., HPX “interactomes,” in a human neutrophil model (promyelocytic HL-60 cells), in hepatoma HepG2 cells, and in primary human hepatocytes. Immunoblots revealed that HL-60 cells lack LRP1, and immunocytochemistry established that HPX trafficked with transferrin and transferrin receptor 1 (TfR1) in Rab5-positive early endosomes, supporting a clathrin-mediated endocytotic pathway used by TfR1s. TfR1 was isolated by heme–HPX affinity chromatography of HL-60 and HepG2 extracts, and similarly, LRP1 from HepG2 cells. These receptors and novel HPX interactome proteins were identified by their peptide sequences. TfR1 downregulation in HL-60 cells in response to holo-human transferrin (Tf) decreased surface binding and intracellular HPX, implicating TfRs in heme–HPX endocytosis. In LRP+/+ HepG2 cells, HPX trafficked in endosomes with LRP1 and TfR1, or with TfR1 alone. HPX co-localized with TfR2, supporting that TfR2 potentially provides liver targeting of heme–HPX in vivo. TfR1 and 2 could both account for apo-HPX recycling. Heme–HPX affinity isolates from primary human hepatocytes contain LRP1 and TfR1. This HPX “interactome” also included proteins associated with hemostasis, inflammation control, coagulation regulation, wound healing, iron transport, and body fluid regulation. The overlapping and distinct roles of TfR1, TfR2, and LRP1 with HPX are reviewed. TfR1 is a scavenger receptor like LRP1; nevertheless, specific hepatic HPX receptors may exist. Increasing knowledge of HPX biology will elucidate the causes that regulate plasma HPX, thus improving clinical and veterinary care. Interestingly, increased understanding of the hematological adaptations to weightlessness that lead to anemia, termed “space anemia,” in astronauts and space tourists may provide new insights into HPX’s role in maintaining iron homeostasis and red cell biology under microgravity conditions as well as upon recovery from space and other anemias.